2022
DOI: 10.3390/ijms23147971
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discovery Using Evolutionary Similarities in Chemical Binding to Inhibit Patient-Derived Hepatocellular Carcinoma

Abstract: Drug resistance causes therapeutic failure in refractory cancer. Cancer drug resistance stems from various factors, such as patient heterogeneity and genetic alterations in somatic cancer cells, including those from identical tissues. Generally, resistance is intrinsic for cancers; however, cancer resistance becomes common owing to an increased drug treatment. Unfortunately, overcoming this issue is not yet possible. The present study aimed to evaluate a clinical approach using candidate compounds 19 and 23, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 74 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…We focused on the signaling pathway of calcium that was enormously induced in sorafenib-resistant PTC cells. Furthermore, there was a slight difference between SERCA isoforms; however, of particular importance was the basal expression level of SERCA , which is an acute regulator of calcium homeostasis and anti-apoptosis [ 24 , 29 , 30 , 31 ]. These were increased in YUMC-R-P1, -P2, and -P3 sorafenib-resistant PTC cells compared with that in sorafenib-sensitive PTC cells, YUMC-S-P1 ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on the signaling pathway of calcium that was enormously induced in sorafenib-resistant PTC cells. Furthermore, there was a slight difference between SERCA isoforms; however, of particular importance was the basal expression level of SERCA , which is an acute regulator of calcium homeostasis and anti-apoptosis [ 24 , 29 , 30 , 31 ]. These were increased in YUMC-R-P1, -P2, and -P3 sorafenib-resistant PTC cells compared with that in sorafenib-sensitive PTC cells, YUMC-S-P1 ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, despite the broadly known anti-cancer efficacy of sorafenib, it did not notably influence human sorafenib-resistant PTC cells. In our published papers, we proposed that metabolic stress-resistant cancer cells evaded apoptosis by cytoplasmic-free Ca 2+ overburden via SERCA increase under severe ER stress conditions [ 31 , 66 , 67 ]. The present study showed that regardless of the extreme increase in SERCA expression in sorafenib-resistant PTC cells, the functional restriction of SERCA by the novel SERCA inhibitors, candidates 24 or 31, could lead to severe ER stress-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the calcium signaling pathways were also highly enhanced in paclitaxel- or sorafenib-resistant PTC cells ( Figure 2 D–F). Furthermore, basal levels of the protein expression of SERCA, which is a critical player in apoptosis and calcium homeostasis [ 23 , 28 , 29 , 30 ], were higher in YUMC-R-P1, -P2, and -P3 than in YUMC-S-P1 cells ( Figure 2 G). Moreover, after exposure to paclitaxel or sorafenib, the levels of expression of SERCA significantly increased in YUMC-R-P1, -P2, and -P3 compared to YUMC-S-P1 cells ( Figure 2 G).…”
Section: Resultsmentioning
confidence: 99%
“…Cell viability was measured using the MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide) assay; cells were seeded in 96-well plates at 7 × 10 3 cells per well and incubated overnight to achieve 80% confluency. The detailed protocol can be found in our previous article [ 30 ]. Data were expressed as a percentage of the signal observed in vehicle-treated cells and are shown as the means ± SEM of triplicate experiments.…”
Section: Methodsmentioning
confidence: 99%
“…This is accomplished by increasing SERCA expression, thereby permitting survival under metabolically challenging conditions. Previously, we demonstrated potential results for applying novel combinatorial strategies and discovering anti-cancer candidates that SERCA-targeted a speci c vulnerability of patient-derived anti-cancer drug-resistant cancer cells [20,21]. However, a cardiac dysfunction was inevitable in xenograft model because of nonspeci c inhibition of SERCA isoforms by several candidates [20,21].…”
Section: Introductionmentioning
confidence: 99%